Impact of Turkish Parents' Knowledge on HPV and HPV Vaccination on Attitudes and Beliefs Regarding the HPV Vaccine: A Cross-Sectional Study - Elif Bakır; Handan Özdemir; Tuğçe Torun (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This study aims to evaluate parents’ knowledge of HPV infections and vaccines, their attitudes and beliefs and the relationship between these factors.Materials and Methods: A descriptive cross-sectional study was conducted in the pediatric clinics of a university hospital, with a total of 206 parents participating. The Human Papillomavirus Knowledge Scale and the Carolina HPV Immunization Attitudes and Beliefs Scale were administered to 50 parents who indicated they were knowledgeable about HPV.Results: The majority of parents (75.7%) were unaware of HPV. Among those who were knowledgeable about HPV, most ensured that their children received the vaccinations included in the national schedule; however, only 1.5% had received the HPV vaccine themselves. As HPV knowledge increased, negative attitudes toward HPV vaccination decreased (p < 0.05). Additionally, linear regression analysis indicated that the HPV knowledge score significantly influenced the Carolina HPV Vaccination Attitudes and Beliefs Scale score (p < 0.05).Conclusion: A significant gap in HPV awareness exists among parents, with many also exhibiting negative attitudes toward vaccination. Targeted interventions that offer personalized approaches may help improve parental confidence, especially among those holding negative attitudes toward vaccination.